Usability of ICT for Class Size Remediation and Learning Among Secondary Schools - Hammed Olalekan Bolaji; Olawale Abayomi Onikoyi (Indonesian Journal of Educational Research and Technology, 2024)
The use of Information and Communication Technology (ICT) for learning and reducing class size in secondary schools in Lagos was examined in this study. Secondary data were utilized in the paper study, and those secondary data came from both print and internet sources. The research identified several issues that prevent the effective administration of ICT in Nigerian secondary schools, including remediation of ICT in secondary such schools as adequate ICT facilities in secondary schools, unstable power supply, high costs of ICT facilities, poor implementation of Government policies on ICT, poor network service and coverage, and low ICT literacy. This research recommends that the government enhance funds for ICT education, provide professional development for teachers and school administrators, provide enough ICT facilities and implement all ICT educational legislation.